Russia and the Former Soviet space : instrumentalizing security, legitimizing intervention - Rotaru, Vasile; Troncotă, Miruna (Cambridge Scholars Publishing, 2017)
This book represents a fresh contribution to the contemporary academic debate regarding the determinants of current Russian foreign policy assertiveness. More precisely, it addresses the ways in which perceived security threats have been used by Russia to legitimize its interventions in the former Soviet Space. It is argued here that the security dimension has been successfully used by the Kremlin for the domestic justification of its aggressive actions in neighbouring countries, and that the narrative of the 'besieged fortress' was applied to both the war in Georgia and the intervention in Uk.